AUDIT INTERNAL KEAMANAN SISTEM INFORMASI KEUANGAN STEKOM MENGGUNAKAN ACUNETIX TOOLS DENGAN STANDART SMKI - Irwan Sembiring; Robby Andika Kusumajaya (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2020)
Security becomes very important in the financial information system, the information security policy should be good and should include several procedures, such as property management, human resources management, physical and environmental safeguards, security logical security, information technology operational security and related incident handling procedures With information systems. Therefore it is necessary to evaluate the security of information systems to ensure information security, especially procedures implemented in accordance with ISO / IEC 27001 procedures. The Information Security Management System (SMKI) becomes a common standard in providing a way that should be implemented in the implementation of security concepts Information from the management aspects of information systems and network security. To measure the threat level of an information system using Acunetix software. With the application of standard ISO / IEC 27001 can protect aspects of information security that is confidentiality, integrity and availability. The purpose of conducting an audit can provide an appropriate way to the security of information systems residing in STEKOM institutions